Intradural sequestration of lumbar disc herniation with cranial migration: a case report - Grigoriy Yu. Evzikov; Mikhail G. Bashlachev; Maksim I. Gaydash (Сеченовский вестник)
Intradural herniation of the intervertebral disc (IHID) is extremely rare. There are only a few reports of cranial migration of an intradural fragment of a sequestered disc herniation.Clinical case. A 51-year-old patient who had previously undergone two operations at L5–S1 and L4–L5 levels was admitted to the hospital with complaints of low back pain with radiation to both legs, numbness in the perineum and inner surface of the thighs, urinary retention, constipation. Magnetic resonance imaging revealed a 30 mm mass located at the level of the L3 vertebral body, within the dural sac and filling its entire transverse diameter. The cauda equina nerve roots were compressed. Surgery was performed: the herniated sequestrum (30×10×10 mm) was separated from the nerve roots fixed to it and removed. After surgery, sensation in the buttocks and inner thighs returned, and urinary urge appeared. Rehabilitation is ongoing.Discussion. In most cases, IHID is diagnosed intraoperatively. In the presented case, the genesis of the formation remained unclear before surgery, so a laminectomy approach was chosen, which allowed for extensive revision of the intradural space, thorough radiculolysis, and identification of the cranial migration of the sequestrated disc herniation. The only effective treatment for IHID is surgery.